2022
DOI: 10.1177/00420980211064455
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of political fragmentation on inclusive economic resilience: Examining American metropolitan areas after the Great Recession

Abstract: We propose the concept of inclusive economic resilience to examine intra-regional economic recovery in American metropolitan areas after the Great Recession. Previous studies have treated regional and municipal economic resilience separately, with little attention to within-region variations in economic resilience. We contribute to the understanding of regional economic resilience by focusing on intra-regional economic recovery in cities. We also introduce an important yet overlooked regional factor in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It involves the ability of a region to resist disruptive shocks, the speed of return to pre-shock performance levels, the extent to which the region adapts its economic structure, and the degree to which the region resumes its pre-shock growth path. The impacts of political fragmentation on inclusive economic resilience have been examined in American metropolitan areas after the Great Recession, contributing to the understanding of regional economic resilience by focusing on intra-regional economic recovery in cities (Lee & Wang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It involves the ability of a region to resist disruptive shocks, the speed of return to pre-shock performance levels, the extent to which the region adapts its economic structure, and the degree to which the region resumes its pre-shock growth path. The impacts of political fragmentation on inclusive economic resilience have been examined in American metropolitan areas after the Great Recession, contributing to the understanding of regional economic resilience by focusing on intra-regional economic recovery in cities (Lee & Wang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cities with stronger economic resilience can effectively resist crises, maintain stability, and even achieve transformation and upgrading. In contrast, cities with weaker economic resilience are more vulnerable and prone to falling into recession crises [11,20]. Therefore, the theory of economic resilience helps elucidate the differentiation of urban development triggered by regional structural crises, thereby providing theoretical support for the dynamic evolution of urban growth and shrinkage [9].…”
Section: Introductionmentioning
confidence: 99%
“…Other scholars have focused on the influence of resource factors, such as infrastructure, human capital, and research institutions, on economic resilience [46,47]. Moreover, several researchers have investigated the influence of institutional environmental factors, specifically policy arrangements, on economic resilience [48][49][50]. Furthermore, new perspectives in economic resilience research, such as technological network structures [51] and industry embeddedness [45], have emerged, providing a deeper understanding of this topic.…”
Section: Introductionmentioning
confidence: 99%